Nationality, Cultural Values and the Relative Importance of Task Performance and Organizational Citizenship Behaviour in Performance Evaluation Decisions - Jiao, Changquan; Hardie, Timothy (Journal of Comparative International Management, 2009)
This study examines managers’ evaluations of overall job performance related to cultural orientations and nationality. Good citizenry enhances the common social welfare of a work unit, whereas task performance emphasizes core activities associated with task completion. Using data collected from both Chinese and Canadian respondents, we found collectivism related positively with good citizenry, which is beneficial to other citizens and organizations. Chinese respondents, as compared with their Canadian counterparts, gave more importance to good citizenship behavior, thinking that it would be beneficial to everyone. The behavioral differences between the nationalities remained strong even after controlling for differences in collectivism and power distance. The implications of this phenomenon into the future research and practices are discussed in this paper.